Industrial robots, their role in manufacturing industry (Organisation for Economic Co-operation and Development, 1983)
This book introduce basic concepts and definitions. Production and supply aspects. Trens in applictions and demand. The impact of industrial robots on industry. Conclusions and policy considerations.